Systematic Literature Review: Pengaruh Komunikasi Interpersonal Terhadap Keberhasilan Kerja Tim - Sholihah, Imro'atus; Khoirinnisa’, Nurul; Milad, Khusnu (Buana Komunikasi (Jurnal Penelitian dan Studi Ilmu Komunikasi), 2025)
This study examines the impact of interpersonal communication on teamwork success through a systematic literature review (SLR) of 15 scientific articles from 2020-2025. The results show that interpersonal communication is very important in building trust, reducing conflict, increasing cohesion, and strengthening team collaboration. With effective communication, team performance increases significantly. This study concludes that interpersonal communication is a strategic aspect in human resource management that supports the achievement of organizational goals through optimal teamwork.